Stop motion video about exclusive breastfeeding on increasing knowledge of third trimester pregnant women - Windu Suciati Rahma; Joko Susilo; Hesty Widyasih (Jurnal Kesehatan Ibu dan Anak, 2022)
WHO and UNICEF state that exclusive breastfeeding helps children survive with antibodies they need. Mother's knowledge about exclusive breastfeeding can be increased through health education. Technology makes information easier to access, especially since the current COVID-19 pandemic has made direct contact communication avoided. This encourages the use of electronic-based learning media which contains visual elements and audio elements in the form of stop motion videos. The aim of this study was to know the effect of stop motion video on increasing knowledge of pregnant women on third trimester pregnant women. This research was a quasi- experimental study with Nonequivalent pre- test and post-test with control group design. This research was conducted from September 2021 until January 2022. The population was third trimester pregnant women who met the inclusion and exclusion criteria. Sample are 18 women for experimental groups and 18 women for the control group. Data analysis using Mann-Whitney. The mean rank of knowledge in the experimental group was 21.81 and, in the control, group was 15.19 with p value = 0.046. This shows that there was an effect of giving intervention both in the experimental group and the control group, but the more influential in this study was the experimental group. There was effect of stop motion video about exclusive breastfeeding on increasing knowledge of pregnant women on third trimester pregnant women.